2022
DOI: 10.1101/2022.10.12.511984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular vesicles from non-neuroendocrine SCLC cells promote adhesion and survival of neuroendocrine SCLC cells

Abstract: Small Cell Lung Cancer (SCLC) tumors are made up of distinct cell subpopulations, including neuroendocrine (NE) and non-NE cells. While secreted factors from non-NE SCLC cells have been shown to support the growth of the NE cells, the underlying molecular factors are not well understood. Here, we show that exosome-type small extracellular vesicles (SEVs) secreted from non-NE SCLC cells promote adhesion and survival of NE SCLC cells. Proteomic analysis of purified small EVs revealed that extracellular matrix (E… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…EVs are important complex signaling players in the tumor microenvironment, interacting not only with diverse cell types to regulate and alter their functions, but further in their dynamic interaction with the extracellular matrix (ECM). Jiminez identified specific cells could synthesize and secrete quantities of ECM that are carried primarily by small EVs [26]. The study identified that protein cargo associated small EVs comprised the ECM factors in cancer cells enhanced adhesion and survival of stem‐like, tumor propagating cells, where the ECM‐carrying EVs from cancer cells induce a morphological shift from cell‐cell to cell‐substrate adhesion.…”
Section: Extracellular Vesicle Proteome Dynamicsmentioning
confidence: 99%
“…EVs are important complex signaling players in the tumor microenvironment, interacting not only with diverse cell types to regulate and alter their functions, but further in their dynamic interaction with the extracellular matrix (ECM). Jiminez identified specific cells could synthesize and secrete quantities of ECM that are carried primarily by small EVs [26]. The study identified that protein cargo associated small EVs comprised the ECM factors in cancer cells enhanced adhesion and survival of stem‐like, tumor propagating cells, where the ECM‐carrying EVs from cancer cells induce a morphological shift from cell‐cell to cell‐substrate adhesion.…”
Section: Extracellular Vesicle Proteome Dynamicsmentioning
confidence: 99%